THE UNCERTAINTY OF TRUTH IN THE DEBATE BETWEEN REALISM AND INSTRUMENTALISM - Muhammad Habib Izzuddin Amin (International Journal of Multidisciplinary Reseach, 2025)
Abstract : The debate between realism and instrumentalism in the philosophy of science has become one of the central topics concerning the nature of scientific truth and the relationship between scientific theories and reality. These two approaches offer contrasting perspectives on the role of scientific theories: realism views scientific theories as accurate representations of an objective world, while instrumentalism regards them merely as tools for predicting phenomena without making ontological claims about their truth. This study employs a literature review and conceptual analysis to compare the realist and instrumentalist viewpoints in the philosophy of science and to identify the uncertainty of truth that arises between them. The aim of this research is to understand the uncertainty of truth within the debate between realism and instrumentalism and its relevance to the development of contemporary science. The findings suggest that the uncertainty of truth is not a weakness of science, but rather an essential feature that allows for the growth and revision of theories. This article aims to contribute to a deeper understanding of the dynamics of the philosophy of science and its implications for scientific practice in the modern era.